2019
DOI: 10.3390/molecules24091808
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Chitosan Dispersion and Microparticles on Older Streptococcus mutans Biofilms

Abstract: (1) Background: The effectiveness of chitosan to improve the action of antimicrobial compounds against planktonic bacteria and young biofilms has been widely investigated in Dentistry, where the biofilm lifecycle is a determining factor for the success of antibacterial treatment. In the present study, mature Streptococcus mutans biofilms were treated with chitosan dispersion (CD) or chitosan microparticles (CM). (2) Methods: CD at 0.25% and 1% were characterized by texture analysis, while CD at 2% was spray-dr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 32 publications
0
12
0
1
Order By: Relevance
“…Costa et al 36 evaluated mouthwashes containing chitosan and concluded that it can decrease the count of S. mutans. Chen and Chung 37 Fujiwara et al, 38 Kawakita et al, 39 and de Paz et al 40 used chitosan dissolved in water as a mouthwash against S. mutans and found similar results. Hayashi et al 23 inhibition of S. mutans and reduction of its count in the saliva following the use of chitosan chewing gum.…”
Section: Discussionmentioning
confidence: 83%
“…Costa et al 36 evaluated mouthwashes containing chitosan and concluded that it can decrease the count of S. mutans. Chen and Chung 37 Fujiwara et al, 38 Kawakita et al, 39 and de Paz et al 40 used chitosan dissolved in water as a mouthwash against S. mutans and found similar results. Hayashi et al 23 inhibition of S. mutans and reduction of its count in the saliva following the use of chitosan chewing gum.…”
Section: Discussionmentioning
confidence: 83%
“…Due to its own antimicrobial activity, chitosan alone in microparticle form has also been investigated. Kawatika et al [160] have compared the effect of chitosan aqueous dispersion and microparticles on mature biofilms of S. mutans and demonstarted that chitosan in microparticle form reduced the bacterial viability and acidogenicity more effectively than the dispersions, thereby was more effective to control the growth of mature biofilms. Moura et al [161] have investigated the release of locally delivered doxycycline-loaded PLGA microspheres in the periodontal pocket of patients with chronic periodontitis.…”
Section: Microparticlesmentioning
confidence: 99%
“…Kawatika et al [156] have compared the effect of chitosan aqueous dispersion and microparticles on mature bio lms of S. mutans and demonstarted that chitosan in microparticle form reduced the bacterial viability and acidogenicity more effectively than the dispersions, thereby was more effective to control the growth of mature bio lms. Moura et al [157] have investigated the release of locally delivered doxycycline loaded PLGA microspheres in the periodontal pocket of patients with chronic periodontitis.…”
Section: Microparticlesmentioning
confidence: 99%